Rehabilitación y Articulación Urbano Paisajística en la Avenida Terreros de Soacha. El Espacio Público Como Sistema Estructurante de la Ciudad (2021)
The purpose of this degree work consists in the improvement of the public space of the axis of the second most important avenue in the municipality of Soacha, Terreros avenue, currently lacking in public space, the axis ends in the Terreros lagoon which It forms part of the main ecological structure of the municipality, however, it lacks urban elements that control the affectations of the urbanizations.